Object Sorting Conveyor with Detection Color Using ESP-32 Camera Python Based on Open-CV - Indah Sulistiyowati; Hafidz Maulana Ichsan; Izza Anshory (JEECS (Journal of Electrical Engineering and Computer Sciences), 2024)
The OpenCV Python library has been developed in all technology fields, including the industrial sector. In the industrial world, there are objects sorting tools in the form of conveyors. These instruments are presently more advanced since they employ cameras to read the things that should be sorted. The purpose of applying the Open Source Computer Vision Library (OpenCV) system to this object’s sorter conveyor is to make it easier to sort objects based on color detection technology. The OpenCV method for object detection based on color was employed to select those objects. The first step in identifying the object in question is to capture RGB (red, green, and blue) objects in real time and transform their colors into HSV. Additionally, by masking the object to be centered and applying a threshold, the morphological process can remove unnecessary noise from the image. The investigation results include the ability to differentiate objects based on RGB color when sorted by considering the HSV value on the surface of colored objects.